PERAN KEBIJAKAN TRANSPORTASI UNTUK MENDUKUNG AKSESIBILITAS DAN MOBILITAS PADA PENGEMBANGAN WILAYAH PERKOTAAN - Ircham, Ircham; Munawar, Ahmad; Munthohar, Imam (FSTPT Indonesia, 2015)
A highly urbanization and private vehicle ownership has led to the development of cities becomes unmanageable as well as tends to be urban sprawl. Moreover, congestion, pollution and fossil fuels consumption are increased, along with the decreasing of the feasibility habitation as well. Therefore, we need to manage its growth by applying the right policies. One of them is green belt, which is rounding the existing city by green area. Furthemore, the developments of new settlement are directed outside the green belt and become satellite cities to the major cities. The increasing of urbanization, make the demand in transportation will be increased as well; the requirements of accessibility and mobility have to be supported to keep them running well. Comparative analysis method is used in this research by determining policy transportation as a result of comparing transport policies from among these countries: China, Dutch, England, Malaysia and Indonesia. Transportation policies that are propossed including: restrictions on the amount of ownership of a vehicle, the construction of facilities ‘park and ride’ outside the green belt and public transport facilities towards the city center using railway or bus station in an integrated area services concept. Thus, it will allow the enhancement of accessibility and mobility of citizens.